2016
DOI: 10.1177/1461444815583491
|View full text |Cite
|
Sign up to set email alerts
|

Getting attention online in election coverage: Audience selectivity in the 2012 US presidential election

Abstract: This study investigates how citizens select election news online. Voluntary national samples (n = 372) browsed a news website featuring four types of election news (horserace, candidates' issue positions, campaign trails, and voters). Their online activities, including article selection and the length of exposure, were unobtrusively measured by behavior tracking software. The results revealed that participants tended to choose issue-based election coverage but avoided news stories about campaign trails. The ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 50 publications
2
17
1
Order By: Relevance
“…Negativity in the form of incivility, rather than prompting engagement (Baumeister et al, 2001; Jang & Oh, 2016; Meffert et al, 2006), discouraged interaction with news. We were able to replicate this effect across different types of online behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Negativity in the form of incivility, rather than prompting engagement (Baumeister et al, 2001; Jang & Oh, 2016; Meffert et al, 2006), discouraged interaction with news. We were able to replicate this effect across different types of online behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies to date have examined whether people choose negative political information in textual settings. Two of the studies investigated whether individuals selected headlines with relatively mild negative words like “accuse,” “oppose,” and “criticize” compared with relatively mild positive words like “praise,” “hail,” and “support” (Meffert et al, 2006, p. 34; see also, Jang & Oh, 2016). Both studies found that people gravitated toward negative headlines.…”
Section: Uncivil and Civil Newsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three main reasons for the prominence of strategic and horse race frames in the news are as follows. First, they correspond with news values such as drama, negativity, and personal focus (Aalberg et al, 2012; Galtung & Ruge, 1965), which generally attract audience attention (Iyengar, Norpoth, & Hahn, 2004; Jang & Oh, 2016; Trussler & Soroka, 2014). Second, the professionalization of political campaigns over the years has led journalists to constantly try to uncover politicians’ hidden strategies of image building and media managing (Patterson, 1993).…”
Section: Strategic News Coverage Of Politicsmentioning
confidence: 99%
“…Over the Past decades, political discourse has shifted its rhetorical focus from parties and issues to candidate-oriented narratives (Bennett, 2012), which emphasize the personality and the charisma of politicians (Balmas and Sheafer, 2010). This does not mean that issue-centered campaigns are without merit or effect; studies have shown that certain issue-based strategies can affect exposure when combined with the right candidate persona (Jang and Oh, 2016). Infographics may introduce a shift to this trajectory, as they are, in essence, issue-oriented rather than candidate—or party—centered.…”
Section: Infographics As Political Toolsmentioning
confidence: 99%